PELATIHAN CARA MENGUKUR KINERJA TENAGA PENJUALAN - Rasyid, Ardiansyah; Puswita Anhar, Dela Asokawati; Puspita, Elizabeth Christinio (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
The strategic role of salespeople in achieving success in selling company products cannot be underestimated. Improving the performance of salespeople is crucial, with the hope that it can make a significant contribution to increasing sales volume and achieving predetermined goals. The focus of this community service activity is to provide assistance to business owners so that they have a deep understanding of sales force performance measurement methods, enabling business owners to optimize their sales. The partner selected for this community service project is a honey business with the brand "Madu Pakcik" located in Jambi. Initial observations of the partner showed a major problem related to sales force performance measurement in the context of partner sales. Therefore, this PKM activity is implemented through an online training method using the Zoom Meeting platform. This training aims to provide partners with a comprehensive understanding of the key aspects of measuring sales force performance. Hopefully, with the knowledge gained through this activity, partners can significantly improve the quality and number of their sales. In addition to providing training, this activity also produces outputs in the form of scientific publications submitted to relevant journals as well as Intellectual Property Rights (IPR). Thus, this project not only has an impact on improving partner performance in practical terms, but also contributes to scientific knowledge and innovation in the field of sales force performance measurement.